From Lollipops to Lidocaine: The Need for a Universal Print-to-Speech Framework. - Cummine, Jacqueline; Cullum, Angela; Aalto, Daniel; Sereda, Tyson; Fleming, Cassidy; Reed, Alesha; Ostevik, Amberley; Cashion-Dextrase, Sienna; Jeffery, Caroline C.; Hodgetts, William E. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2021)
Objective: There is a strong relationship between reading and articulation (Lervåg & Hulme, 2009; Pan et al., 2011). Given the tight coupling of these processes, innovative approaches are needed to understand the intricacies associated with print-speech connections. Here we ran a series of tightly controlled experiments to examine the impact of mouth perturbations on silent reading. Method: We altered the mouth, via somatosensory feedback, in several ways: (a) a large lollipop in the mouth (E1), (b) a candy stick (bite bar) held horizontally between the teeth (E2), and (c) lidocaine that served to numb the mouth (E3). Three tasks were completed: (a) picture categorization, (b) "spell" lexical decision (Spell-LDT; "does the letter string spell a real word, yes or no?"), and (c) "sound" lexical decision (Sound-LDT; "does the letter string sound like a real word, yes or no?"). Participants (N = 97; E1 = 27; E2 = 32; E3 = 38) completed each of the tasks two times: once with a somatosensory perturbation (lollipop, bite bar, or lidocaine) and once without. Results: For each experiment, a linear mixed effects analysis was run. Overall, we found that the lollipop (E1) and lidocaine (E3) had some specific effects on word recognition (e.g., for "no" responses), particularly in the Spell-LDT, whereas the bite bar (E2) had no effect on word recognition. The picture categorization task was not impacted by any perturbations. Conclusion: These findings provide evidence that sensorimotor information is connected to reading. We discuss how these findings advance our understanding of a print-to-speech framework.